2021
DOI: 10.21010/ajid.v15i2s.3
|View full text |Cite
|
Sign up to set email alerts
|

Generating Responses Immune in Cellular and Humoral Treatment With Epitope Spike, Epitope Envelope Protein, and Epitope Membrane Protein Sars-Cov-2, Honey, Saussurea Lappa, and Nigella Sativa

Abstract: Background:Covid-19 has become pandemic in the World, including Indonesia. Our last study showed that HSF could serve as an immunomodulator. Using the exact search, we found that the most immuno-dominant SARS-COV2 epitope, namely A spike protein epitope, B envelope protein epitope, and C membrane protein epitope, we concise to be HF Materials and Methods:We used to post only control design study and mice as an animal model. The research divided mice into four groups, and the first group as control received PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…Currently, we found no studies that prove the effectiveness of Saussurea lappa immunomodulating effect in candidiasis infection. Research on immunomodulating effect of Saussurea lappa combined with honey and Nigella sativa was carried out against SARS-COV-2 virus, and found that the combination increased components of immune system which also have a role against fungal pathogens, namely Th17, IL -17A, and β-defensins [18]. Therefore, this may also have to be considered as other potential mechanism of Saussurea lappa root extract in modulating immune system against Candida albicans.…”
Section: Possible Antifungal Mechanism Of Saussurea Lappamentioning
confidence: 99%
“…Currently, we found no studies that prove the effectiveness of Saussurea lappa immunomodulating effect in candidiasis infection. Research on immunomodulating effect of Saussurea lappa combined with honey and Nigella sativa was carried out against SARS-COV-2 virus, and found that the combination increased components of immune system which also have a role against fungal pathogens, namely Th17, IL -17A, and β-defensins [18]. Therefore, this may also have to be considered as other potential mechanism of Saussurea lappa root extract in modulating immune system against Candida albicans.…”
Section: Possible Antifungal Mechanism Of Saussurea Lappamentioning
confidence: 99%